Efektivitas penggunaan lagu dalam menghafal tasrif - Sholihah, Mar’atus (Maliki Interdisciplinary Journal, 2024)
The majority of students find it difficult and bored in learning shorof science, many students memorize tasrifan with songs but the vowel and length are not appropriate. This study aims to determine the level of effectiveness of using songs in memorizing tasrif at MI Islam Malang. This type of research is quantitative research with experimental types. Data obtained through test techniques, interviews, observation and documentation. Grade 5 students totaling 24 students became the source of data in this study. The data analysis technique used was statistics with SPSS software version 29. The results of this study indicate that learning and memorizing tashrif with songs has a stronger and more effective memorization effect than learning and memorizing without songs. This is proven from the calculation of the Wilcoxon test, the Z value obtained for the pretest and posttest of the experimental class is -3.093, while the Z value obtained for the pretest and posttest of the control class is -2.209. The experimental class has a p value (Asymp. Sig 2-failed) of 0.002 which is less than the research critical limit of 0.05, while the control class has a p value (Asymp. Sig 2-failed) of 0.027 which is less than the research critical limit of 0.05 . So that the decision of the hypothesis is that Ha is accepted or means that there is a significant difference in the increase in students’ mastery of memorizing shorofs before and after treatment. For shorof teachers it is recommended to use songs in tasrif learning so that students’ memorization is stronger